Employee Performance Reviewed By The Perspective Of Employee Appreciation - Zahroh, Zahroh; Rido Junianto, Fikri; Tibrani Baariq, Jinan (CV. AFDIFAL MAJU BERKAH, 2024)
This study aims to analyze employee performance in terms of compensation variables and career development in PDAM Tirta Giri Cirebon. This type of research uses a multiple regression analysis. 58 respondents were given questionnaires as part of the research methodology, which employed quantitative techniques and primary data. Multiple regression is employed in the analytical technique, along with hypothesis testing with statistical test t for testing partial regression coefficients and statistical test f for evaluating the effect concurrently at a 5% level of significance. The variables in this study are Career Development (X1), Compensation (X2) which is the perspective of employee appreciation and also the variable Employee Performance (Y). The results of this study show that there is a significant influence both simultaneously and partially between Career Development and Compensation on Performance.